АЗЫҚ-АЎҚАТ АТАМАЛАРЫНЫҢ ДИАЛЕКТЛИК ӨЗГЕШЕЛИКЛЕР МЕНЕН ҚОЛЛАНЫЛЫЎЫ - Қурбанбаева, Б.Р. (FAN va JAMIYAT, 2020)
The article is devoted to the study of dialectical words denoting national dishes in different regions of the Repablic of Karakalpakstan.